Self-Control with Online Shopping Consumptive Behavior in Young Women in Oesapa Village - Valen Florenci Boru; M.Dinah Charlota Lerik; M.K.P Abdi Keraf (Universitas Nusa Cendana, 2021)
Adolescents have unrealistic characteristics, unstable emotional states, and are easily influenced. In this situation, the ability to control themselves becomes weak, so they tend to take action based on emotions, one of which is consumptive especially for young women who shop more frequently. Consumptive behavior is made easier by online shopping. The purpose of this study was to determine the relationship between self-control and consumptive online shopping behavior among young women living in Oesapa Village. This research is a quantitative study with data analysis using the Spearman correlation technique. Determination of the research sample using the Krijcie-Morgan table (1970) with a 95% level of confidence in the population, with a total sample of 341 young women in Oesapa Village; Consumptive Behavior, Self Control, Young Women